Measurement of nitrogen oxide (NOx) emissions in fuel-combustion equipment and analysis of their impact on city air condition - Ivasenko, Vitaliy (Technology audit and production reserves, 2023)
The object of the research is to ensure environmental safety and maximum efficiency of fuel burning equipment. Energy facilities (thermal power plant, boiler houses) are among the biggest air polluters in the city. Nitrogen oxides (NO, NO2, NOx) occupy a significant place among the toxic gases contained in the flue gases of fuel-burning equipment. These substances have a negative impact on the ecological state of the city and are regulated by the Order of the Ministry of Natural Resources of Ukraine dated 27.06.2006 No. 309 on the approval of standards for maximum permissible emissions of pollutants from stationary sources. The principles of measurement unity are considered, including the presentation of measurement results in standard units (ppm, mg/m3). Conversion from volume concentration (ppm) to mass (mg/m3) is given. Measurements of the concentration of nitrogen oxides were carried out. In the course of research, instrumental measuring tools were used, which made it possible to obtain the values of nitrogen dioxide concentrations in gas boiler flue emissions. In particular, the average maximum concentrations of the main pollutants exceed 62.58 mg/m3. Analyzing the concentration of flue gases allows to determine the concentration of pollutants and to adjust the optimal operation of the equipment as much as possible, achieving a reduction in emissions and compliance with the approved emission standards. Obtained data on background concentrations of nitrogen dioxide in the city of Kyiv, amounting to 1.33 MPC. Using the data of instrumental measurements with the method of calculating concentrations of harmful substances in the atmospheric air and background concentrations, a map of emission dispersion was created. Fields of surface concentrations were plotted on the scattering map, which makes it possible to compare the obtained values with the hygienic standards of atmospheric air. By combining instrumental measurement methods and calculation methods, the volume of emissions was determined and the impact on atmospheric air pollution of the city was assessed.